2009
DOI: 10.1209/0295-5075/87/61001
|View full text |Cite
|
Sign up to set email alerts
|

Some peculiarities in response to filling up the Fermi sphere with quarks

Abstract: Considering quarks as the quasi-particles of the model Hamiltonian with four-fermion interaction we study response to the process of filling up the Fermi sphere with quarks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 24 publications
(25 reference statements)
5
27
0
Order By: Relevance
“…The next curves and the ones following upwards correspond to temperatures T = 10 MeV, T = 50 MeV (an upper curve) with a step T = 10 MeV. Let us also remember that the pressure of the vacuum for the NJL model was estimated in [9][10][11] to be 40-50 MeV/fm 3 , which is quite consistent with that obtained in the bag model. It was also demonstrated that there is a region of instability within a certain interval of the Fermi momenta generated by the anomalous behavior of pressure d P/dn < 0 (see also [33][34][35][36]).…”
Section: Mean Energy As a Functional Of Quantum Liquid Theorysupporting
confidence: 79%
See 3 more Smart Citations
“…The next curves and the ones following upwards correspond to temperatures T = 10 MeV, T = 50 MeV (an upper curve) with a step T = 10 MeV. Let us also remember that the pressure of the vacuum for the NJL model was estimated in [9][10][11] to be 40-50 MeV/fm 3 , which is quite consistent with that obtained in the bag model. It was also demonstrated that there is a region of instability within a certain interval of the Fermi momenta generated by the anomalous behavior of pressure d P/dn < 0 (see also [33][34][35][36]).…”
Section: Mean Energy As a Functional Of Quantum Liquid Theorysupporting
confidence: 79%
“…It is the latter that is implied in a scenario of chiral invariance restoration under extreme temperatures higher than 100 MeV and with a highly diluted quark ensemble. We have already noted (see also [9][10][11]) that the momentum p θ , which corresponds to the strongest quark-antiquark attraction d sin θ/d p = 0, …”
Section: Mean Energy As a Functional Of Quantum Liquid Theorymentioning
confidence: 91%
See 2 more Smart Citations
“…These and some related topics are discussed in this paper, inspired by the well-known and fruitful idea about the specific role of surface degrees of freedom in the finite Fermi-liquid systems [3] and, to a considerable extent, by our previous works [4,5] in which the quarks were treated as the quasiparticles of the model Hamiltonian, and the problem of filling up the Fermi sphere was studied in detail. In particular, within the NJL model [6] new solution branches of the equation for dynamical quark mass as a function of chemical potential (the details are shown below in Fig.…”
Section: Introductionmentioning
confidence: 99%